Impact of Implementation of Halal Tourism in West Nusa Tenggara Province: Maqashid al-Sharia Perspective - Abdul Rachman; Bilaly Sangare (Justicia Islamica, 2023)
This study aims to analyze the benefits and harms of implementing Halal Tourism in West Nusa Tenggara Province from the perspective of maqashid al-sharia. This study uses a qualitative method with a phenomenological approach and holistic Fiqh theory. The phenomenological approach is carried out to analyze social phenomena after implementing halal tourism. The Fiqh theory approach focuses more on Islamic law within the scope of maqashid al-sharia. The results of the study state that the impact of halal tourism in West Nusa Tenggara Province on the community, tourists, and the government is dominated by benefit rather than benefit. The impact of halal tourism from the perspective of maqashid al-sharia can be seen from indicators in maintaining religion (hifdz ad-din) in halal tourism, namely the convenience for tourists with the availability of prayer facilities in each destination. In protecting life (hifdz an-nafs), local governments are increasing the number of halal certifications, localization of Halal tourism destinations, and restrictions on alcoholic beverages. In maintaining reason (hifdz al-'aql), the role of the community in developing halal tourism is carried out through Islamic boarding schools. In protecting offspring (hifdz an-nasl), tourists and the public can use several sharia-compliant lodging accommodations such as the Syariah Motel and the Grand Madani Syariah Hotel. Meanwhile, in protecting assets (hifdz al-maal), the community and government provide halal businesses and Islamic financial institutions such as Bank NTB Syariah. The contribution of this article is a guide for the government in making policies and regulations for the implementation of halal tourism in Indonesia.